2018
DOI: 10.1039/c7me00092h
|View full text |Cite
|
Sign up to set email alerts
|

Anti-viral RNAi nanoparticles protect shrimp against white spot disease

Abstract: Nearly 20% of cultured shrimp die every year due to viral diseases. In this study, we evaluated the capacity of nanoparticulate RNA interference (RNAi) to down-regulate genes in Penaeus vannamei shrimp and protect shrimp against white spot syndrome virus (WSSV, i.e. white spot disease).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 49 publications
0
13
0
1
Order By: Relevance
“…Chitosan/dsRNA nanoparticles were first developed to facilitate oral RNAi in Anopheles gambiae larvae 19 . The nanoparticles have been used to facilitate oral RNAi in Aedes aegypti larvae, 32,33 Chilio suppressalis larvae, 30 Chironomus tentans larvae, 34 Penaeus vannamei shrimp, 35 and Caenorhabditis elegans nematodes 36 . In C. suppressalis , chitosan/dsRNA nanoparticles enhanced dsRNA stability and uptake, resulting in enhanced RNAi efficiency 30 .…”
Section: Discussionmentioning
confidence: 99%
“…Chitosan/dsRNA nanoparticles were first developed to facilitate oral RNAi in Anopheles gambiae larvae 19 . The nanoparticles have been used to facilitate oral RNAi in Aedes aegypti larvae, 32,33 Chilio suppressalis larvae, 30 Chironomus tentans larvae, 34 Penaeus vannamei shrimp, 35 and Caenorhabditis elegans nematodes 36 . In C. suppressalis , chitosan/dsRNA nanoparticles enhanced dsRNA stability and uptake, resulting in enhanced RNAi efficiency 30 .…”
Section: Discussionmentioning
confidence: 99%
“…Other studies by IM injection of chemically modified chitosan nanoparticles loaded with anti-VP28 RNA [20] and antisense plasmid constructs for VP28 [24] have shown protection of 95% and 90%, respectively. However, in all these treatments the shrimp exposed to WSSV finally died at 14 dpi.…”
Section: Discussionmentioning
confidence: 95%
“…The antiviral response of RNAi is triggered by double-stranded RNA (dsRNA) to block the synthesis of a specific viral protein, in the case of WSSV the targets being the structural proteins VP19, VP24, VP26, and VP28, as they are involved in cell recognition, virus entry, binding and assembly of the virion. Previous studies have shown that silencing these structural proteins in WSSV challenge assays, increases shrimp survival [10,11,[17][18][19][20][21]. The VP28 glycoprotein plays an important role in systemic infection by interacting with cell membrane proteins, and it is one of the most abundant proteins along with VP26 (≈60%) in the external WSSV surface [21,22].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…7,8 One other proposed approach is to use NANOparticulate RNA interference (RNAi) formulations to downregulate genes that facilitate the viral progression. 9 Although such studies produced promising results in vitro against coronavirus, their efficacy in vivo (as well as in clinic) is yet to be explored. Considering that viruses could be phylogenetically unrelated and structurally different, and given that most vaccines are virus specific, a promising approach would be that of developing broad-spectrum anti-viral NANOparticles to fight COVID-19 and future pandemics.…”
Section: Nano-based Anti-virals As Potential Alternatives?mentioning
confidence: 99%